Herz & Gesundheit - Mastnak W (Dynamic Media Sales Verlag, 2018)
Both for the promotion of health and in long-term rehabilitation of various diseases, precisely shaped and individually adjusted physical exercises are an efficacious means. In this context, sustainable adherence is a crucial problem and involves psychological issues of motivation and self-concepts.Based on spontaneous verbal messages during trainings, micro-interviews, and short-term focus groups, the present qualitative multi-centred study used data from heart patients in long-term cardiac rehabilitation in Austria (n=307) and from students of music and performing arts in Germany (n=386) who enrolled in courses for the promotion of health and the prevention of musculoskeletal problems. Investigating individual incentives to adhere in sports and health-related physical exercises resulted in the sport psychological notion of sport identity that differs from conventional athlete identities. Regrouping comparable data identified four determining factors, i.e., (i) discipline preference, (ii) modality of exertion experience, (iii) the body-self, and (iv) the grade of domination. Being considered a hypothesis generating study, the associated theoretical framework shall help therapists, educators, coaches in public health domains, and practitioners in rehabilitative areas to better understand the individual attachment to sports and to provide activities that are tailored to individual demands. This should enhance adherence and sustainability and avoid risks of discouragement, dependence on external incentives, and reluctance. KEY WORDS: Athletic Identity, Sport Identity, Motivation in Sport, Self-Concept, Health Promoting Sports